SAT0027 DEVELOPMENT AND VALIDATION OF A NOMOGRAM COMBINING CLINICAL AND HISTOPATHOLOGICAL SYNOVIAL FEATURES FOR PREDICTING EARLY TREATMENT RESPONSE IN NAIVE TO TREATMENT RHEUMATOID ARTHRITIS. (2nd June 2020) - Alivernini, S.; Tolusso, B.; Gessi, M.; Gigante, M. R.; Mannocci, A.; Petricca, L.; Perniola, S.; DI Mario, C.; Fedele, A. L.; Bui, L.; Capacci, A.; Bruno, D.; et al.
Abstract : Background: Rheumatoid Arthritis (RA) is characterized by synovial tissue (ST) heterogeneity at disease onset in terms of inflammatory degree and microanatomical organization being related to treatment response. Objectives: To develop a multiparametric tool for baseline treatment response prediction including disease characteristics and histopathologic features of ST biopsies, using a large single center (SYNGem Unit) naive to treatment RA cohort. Methods: 240 naive to treatment RA who underwent US-guided ST biopsy, at the first clinical evaluation, were enrolled. Clinical and immunological characteristics were recorded for each patient. All ST FFPE specimens were stained with H&E and classified by a pathologist, blinded to clinical characteristics, using the Krenn score [1] to assess the degree of ST inflammation. All naive to treatment RA were treated according to the T2T scheme and DAS remission rate at 6-12 months was recorded. On the basis of the regression analysis, a nomogram was constructed that incorporated the significant factors predicting the "achievement of DAS-Remission at 6 months follow-up" in naive RA. The performance of the nomogram was assessed by discrimination and calibration. Results: Univariate analysis showed that RA who achieved early (6 months) DAS-remission had, at baseline, significantly lower total Krenn score (p<0.001), shorter symptoms duration (p=0.005) and lower disease activity (p<0.001) than RA not achieving this clinical outcome. ROC curve analysis revealed that RA having, at baseline, a total Krenn score <4.5 [(AUC)95%C.I.: 0.67(0.60-0.74), p<0.001] achieved more likely DAS-remission at 6 months (53.1%) than RA with total Krenn score ≥4.5(28.9%, p<0.001). Interestingly, RA whose ST was biopsied within 3 months from joint symptoms beginning showed significantly lower ST inflammation as total Krenn score than RA whose ST was analyzed among 3-12 months (p=0.04) or after 12 months (p=0.002) since symptoms beginning. However, in terms of follicular structure presence, the microanatomical organization of the synovial inflammatory infiltrate did not differ comparing RA whose ST was biopsied within 3 months from joint symptoms beginning (44.4%) and RA whose ST was biopsied among 3-12 months (47.6%, p=0.74) or after 12 months (52.7%, p=0.33) since symptoms beginning. Logistic regression analysis revealed that, at baseline, being VERA, not having HDA and having a total Krenn score <4.5 were synergistic factors of DAS-remission achievement at 6 months [OR:10.5(95%IC:2.28-48.01);p<0.05]. Based on the regression analysis, a nomogram integrating baseline clinical (disease activity and duration) and histological (total Krenn score) characteristics was developed in which the value of each of the variables was given a point score. A total score was calculated by adding each single point score and, by projecting the value of the "total points" score to the "probability" line up to 87.5%. Conclusion: Krenn score is a reliable tool for the semi-quantitative assessment of ST inflammation on US-guided ST biopsies being contingent to baseline disease characteristics and can be integrated within a nomogram to better predict the therapeutic response in naive to treatment RA. References: [1] Krenn V, et al. Histopathology 2006 Disclosure of Interests: Stefano Alivernini: None declared, Barbara Tolusso: None declared, Marco Gessi: None declared, Maria Rita Gigante: None declared, Alice Mannocci: None declared, Luca Petricca: None declared, Simone Perniola: None declared, Clara Di Mario: None declared, Anna Laura Fedele: None declared, Laura Bui: None declared, Annunziata Capacci: None declared, Dario Bruno: None declared, Giuseppe La Torre: None declared, Francesco Federico: None declared, Gianfranco Ferraccioli: None declared, Elisa Gremese Speakers bureau: Abbvie, BMS, Celgene, Jannsen, Lilly, MSD, Novartis, Pfizer, Sandoz, UCB